A Model for Developing Usable Integrated Case Management Information Systems - Kuhimbisa, Edgar; Baguma, Rehema; Nakakawa, Agnes (Springer International Publishing, 2017)
The increased adoption of technology in government-driven processes and services over the years has led to the use of information and communication technologies (ICTs) as mechanisms and platforms for citizens to access justice services and participate in the judicial process. In Uganda, there are current and ongoing efforts, through e-justice initiatives in the Justice, Law and Order Sector, to integrate case management information systems in criminal justice institutions as a means of improving worker productivity, facilitating information sharing, collaboration, better information access by the general public, citizen engagement and satisfaction with public services. The focus for this study was to devise a model that provides guidance on how to develop integrated information systems that are usable – by supporting improved human-driven legal processes, increased citizen engagement and facilitation of interaction between justice agencies and the general public. Based on the requirements for usable integrated information systems obtained from the review of literature and a survey, a model for guiding development of usable integrated case management information systems known as the Architecture-driven Usability Process Model (AdUPRO) was created.
Keywords: Usability; Integrated information systems; Case management; E-Justice